Aplikasi Proses Hierarki Analitik dan SistemMaklumat Geografi dalam Penilaian KesesuaianPrasarana Pendidikan di Kuala Lumpur: Application of Analytical Hierarchy Process and GeographicalInformation System in Education Infrastructure SuitabilityEvalution in Kuala Lumpur - Md. Hashim, Noorazuan; Ibrahim, Yusof; Nayan, Nasir; Che Ngah, Mohamad Suhaily Yusri; Hashim, Mohmadisa (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2011)
The modernization of education infrastructure and facilities will continue to be the most important development agenda in Malaysia. However, issues related to location of schools and its suitability often ended up with debates within the stakeholders. The selected location of school seldomly rejected by the locals. This study attempts to assess the suitability of existing primary schools in Strategic Zone of Sentul-Manjalara. The study highlights education planning and infrastucture development in the strategic zone. Seven locations with suitable parameters including sizes and school sites as well as class-room class ratio have been selected into analysis. Analytic hierarchy process or AHP method. The Multi Criteria Decision Analysis was used to developed score and weight for each parameter. Based on 47 existing schools, only 20 schools were considered between good to best suitable school category, where as the balance (i.e. 27 schools) were considered to be between moderate to less suitable school category. In this study, the AHP application has produced integrated and efficient result in analysing the school’s location and its suitability. However, expert views from various departments has to be considered in order to verify and validate the findings for future upgrading and application